Memoria multidireccional, elaboración y danza en Chungui: horror sin lágrimas, de Luis Felipe Degregori (2009) - Torres-Astocóndor, Carlos (2025)
This paper analyzes, from the perspective of memory studies, the documentary Chungui: horror sin lágrimas, by Luis Felipe Degregori (2009). Through the categories of multidirectional memory (Rothberg, 2009), acting-out and working-through (LaCapra, 2001/2005), I argue that the narrating voice in the film resorts to the images and the scriptural work of Guamán Poma de Ayala’s Nueva corónica y buen gobierno (1615/1980) to establish a historical connection between the colonial and republican stages in regards to the prejudicial treatment against Andean communities by colonial and, later, state authorities. With this relationship, the documentary expands the denunciation of the human rights violations perpetrated against the Chungui community during the years of political violence in Peru (1980-2000). In this way, the memory during the political violence and the colonial memory written by Guamán Poma de Ayala establish dialogic interactions and affirm a continuity in relation to the damage and violations to the detriment of the Indigenous population. Likewise, I argue that the llaqta maqta, a particular dance of the Chungui people included in the final part of the documentary, is a cultural practice of resistance that allows, by a process of working-through, to critically relate to the trauma that the Chungui population suffered during the years of political violence.